Vlbrotactile perception as a test for numbness and pain - Brammer, Anthony J.; Sutinen, Paivi; Das, Sourish; Pyykko, Ilmari; Toppila, Esko; Starck, Jukka (Canadian Acoustics, 2009)
A study was conducted to demonstrate a vibrotactile test to assess the presence or absence of sensory symptoms in the hands. The investigations were based on perception thresholds that mediated selectively by different types of mechanoreceptors. The test was constructed from the summed differences between the the thresholds recorded at the fingertip of an individual and the mean values of the threshold for healthy persons at the same simulation frequencies. The metric was found to be related to reports by subjects of numbness and pain using two statistical tests for evaluating the significance of associations in 2×2 contingency tables. The performance of the test was evaluated by adjusting the magnitude of the metric to serve as the boundary for the onset of symptoms by individual subjects.